Turning parameters optimisation for Inconel 800H under MQL environment based on Harris hawks optimisation algorithm coupled with TOPSIS method. (14th March 2023) - Bharath, H.; Venkatesan, K.; Devendiran, S.
In this study, turning operations were performed to optimise the surface roughness, cutting force, and residual stress. Trials were done on Inconel 800H using olive oil mixed with 0.20 wt % hexagonal boron nitride. Response surface methodology has established a link between input and machining responses. Harris hawk optimisation (HHO) was used to search for potential candidates for the solution. A technique for order preference by similarity to the ideal solution (TOPSIS) was used to detect the most viable compromise. The optimal results of TOPSIS-HHO are benchmarked with other metaheuristic algorithms. The results show that the optimum results and their responses found through experiments are Ra 0.2837 µm, Fz 137 N, and Res 406 MPa, which are less than a 10% average error on the predicted value. The HHO-TOPSIS showed an improvement in convergence rate by 9.57%, 12.04%, 11.73%, and 32.65% at the optimal determined values compared to other hybrid algorithms.